2010
DOI: 10.1016/j.febslet.2010.05.041
|View full text |Cite
|
Sign up to set email alerts
|

Erratum to “Curcumin inhibits hepatitis B virus via down‐regulation of the metabolic coactivator PGC‐1α” [FEBS Lett. 584 (2010) 2485–2490]

Abstract: ErratumErratum to ''Curcumin inhibits hepatitis B virus via down-regulation of the metabolic coactivator PGC-1a" [FEBS Lett. 584 (2010) In the last stages of the production process of the printed version, after the authors' proof had been returned, an unfortunate error was made in the list of the names of authors. The correct names and affiliations are given above.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(26 citation statements)
references
References 0 publications
0
25
0
1
Order By: Relevance
“…Its multiple-target characteristics influence several activities of intracellular molecules, including transcription nuclear factor-κB (NF-κB), pro-inflammatory cyclooxygenase-2 and MAPK inhibitions, as well as heme oxygenase-1 induction (9). In the antivirus bioactivity, certain reports have indicated that curcumin showed anti-viral activity against the human immunodeficiency (10,11), the coxsackie- (12) and the hepatitis B (HBV) viruses (13). In the anti-HCV study, one report showed that curcumin inhibited a lipogenic transcription factor, sterol regulatory element binding protein-1 (SREBP-1)-induced HCV replication via the inhibition of the PI3K-AKT pathway (14).…”
Section: Introductionmentioning
confidence: 99%
“…Its multiple-target characteristics influence several activities of intracellular molecules, including transcription nuclear factor-κB (NF-κB), pro-inflammatory cyclooxygenase-2 and MAPK inhibitions, as well as heme oxygenase-1 induction (9). In the antivirus bioactivity, certain reports have indicated that curcumin showed anti-viral activity against the human immunodeficiency (10,11), the coxsackie- (12) and the hepatitis B (HBV) viruses (13). In the anti-HCV study, one report showed that curcumin inhibited a lipogenic transcription factor, sterol regulatory element binding protein-1 (SREBP-1)-induced HCV replication via the inhibition of the PI3K-AKT pathway (14).…”
Section: Introductionmentioning
confidence: 99%
“…All cell lines were grown at 37 °C under a 5% CO2 atmosphere. HEK293T cells were transfected by using CaHPO 4 method as previously described [18,19]. Transfection efficiency was evaluated by GFP visualization 24 h after transfection.…”
Section: Methodsmentioning
confidence: 99%
“…Nevertheless, some promising observations have been made in cell culture and mouse model experiments. Several HDAC inhibitors have been shown to decrease cell proliferation , increase apoptosis , and to decrease both lipogenesis and gluconeogenesis . These effects could be beneficial for anti‐HCC treatment in HBV‐positive patients.…”
Section: Future Hepatitis B Treatment Optionsmentioning
confidence: 99%